The Relationship Between Moral Sensitivity Levels and Professional Values of Nursing Students - Eylem Paslı Gürdoğan; Berna Aksoy; Ezgi Kınıcı (Association of Nurse Managers, 2018)
INTRODUCTION: This study was conducted to determine the level of moral sensitivity and opinions about importance of provessional values of nursing students and to investigate the relationship between them. METHODS: This descriptive study's universe consisted of first, second, third, and fourth grade students (N=512) who read the Nursing Department of Health Sciences Faculty of a state university. Students (n=334) who voluntarily accepted to participate constituted the sample of the study. Data were collected with a questionnaire form consist of questions about the socio-demographic characteristics of students and perceptions of the importance of professional values and the Moral Sensitivity Questionnaire. RESULTS: The average age of the students was 20.5+-1.57 and 34.7% of them was the first class student. 69.8% of the students voluntarily selected the profession, and 54.5% faced ethical dilemmas during clinical practice. The total score of the moral sensitivity questionnaire was 76+-16.05 and there was a statistically significant difference between gender and grades of the students (p<0.05). The first three professional values that students consider to be extremely important were accuracy (58.4%), equality (57.5%) and freedom (53.6%). There was a statistically significant difference between importance of the aesthetic value and moral sensitivity scale scores of student's. (p<0.05). DISCUSSION AND CONCLUSION: Nursing students have a high moral sensitivity and they they give a high degree of importance to professional values such as accuracy, equality and freedom.